2012
DOI: 10.1016/j.surfcoat.2012.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Optical and mechanical characterization of novel cobalt-based metal oxide thin films synthesized using sol–gel dip-coating method

Abstract: ÔØ Å ÒÙ× Ö ÔØOptical and mechanical characterization of novel cobalt-based metal oxide thin films synthesized using sol-gel dip-coating method This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 44 publications
6
38
0
Order By: Relevance
“…Preparation of the cobalt copper oxides thin film coatings was conducted as reported in our previous study [14] Cu/Co molar ratio of 0.5, 1 and 2) were mixed using absolute ethanol. Propionate acid was subsequently added to the solution as a complexing agent and stirred for 2 hours.…”
Section: Preparation Of Thin Film Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of the cobalt copper oxides thin film coatings was conducted as reported in our previous study [14] Cu/Co molar ratio of 0.5, 1 and 2) were mixed using absolute ethanol. Propionate acid was subsequently added to the solution as a complexing agent and stirred for 2 hours.…”
Section: Preparation Of Thin Film Coatingsmentioning
confidence: 99%
“…In order to harness the beneficial properties of such metal oxides, we had, therefore, conducted deposition of new cobalt-based metal oxide thin films (M x Co y O z with M = Mn, Cu, Ni) on commercial aluminum and glass substrates using sol-gel dip-coating method [14]. Our study revealed that Cu x Co y O z thin film coatings exhibited favourable optical properties, albeit it was clear that further optimization study would be required to facilitate commercialization of these coatings.…”
Section: Introductionmentioning
confidence: 99%
“…The absorptance of 83.4% (prior to the addition of an antireflection layer) was accomplished using 0.25 M copper acetate and 0.25 M cobalt chloride (Cu/Co ratio=1) with dip-speed 120 mm/min (four cycles). Nanoindentation test using the Berkovich indenter showed that the coatings have a high wear resistance [115][116][117].…”
Section: Cumno X Spinels and Cu X Co Y O Z Spinel-likementioning
confidence: 99%
“…This is quite surprising, in view of the fact that mechanical strength and durability are important in extending their service life. In our previous work, the copper cobalt oxide thin films were deposited on aluminium substrate via the sol-gel dip-coating route [19,20,21]. The resulting coatings exhibited distinctive optical properties with a spectrally selective profile in the UV-Vis-NIR wavelengths region.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%